Supraventricular tachycardia at 37 weeks with electro cardioversion therapy - S., Donel; Adhar L., Munawar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
The health of both the mother and the fetus is at risk when symptomatic maternal arrhythmias occur during pregnancy. Sustained symptomatic arrhythmias should be managed, much like in the non-pregnant population. The specific arrhythmia that has been identified or is suspected must be treated. Electrical cardioversion (ECV) is used to treat supraventricular arrhythmias when medication therapy and physical therapy, such as sinus carotid massage or Valsalva movements, fail or in life-threatening conditions where the patient is hemodynamically unstable. A 27-year-old primipara came to Bengkalis hospital at 37 weeks of gestation due to complaints of palpitations. palpitations felt since 4 hours before admission to the hospital. The patient had experienced the same complaint and was examined by a cardiologist who said that the patient had a tendency to arrhythmia and was given bisoprolol. An ECG examination was carried out in the emergency room, the impression was supraventricular tachycardia with HR 185 bpm, an abdominal termination of pregnancy was carried out, and the cardiologist performed electro-cardioversion (ECV) in the operating room 3 times, and the mother’s HR returned to sinus rhythm. The outcome was a baby girl born with a birth weight of 3200 grams, an Apgar score of 8/9. Mother was treated and went home on the 3rd post-operative day in good condition. Provided that a multidisciplinary approach, continuous fetal heart rate monitoring and the possibility to perform a caesarean section are applied, it can be concluded that cardioversion is a safe and effective treatment for maternal tachycardia in pregnancy.